(untitled) (Italiano LinguaDue, 2023)
Questo lavoro presenta un modello pragmatico-cognitivo di analisi del fenomeno della vaghezza linguistica in quanto strategia implicitante persuasiva e potenzialmente manipolatoria. Nel nostro studio delineeremo la differenza tra i concetti di vaghezza sistemica, vaghezza soritica e vaghezza intenzionale. Quest’ultima sarà il focus delle nostre analisi. Il lavoro introduce la nozione di vaghezza implicitante, e presenta una panoramica sulle funzioni principali della vaghezza intenzionale, mostrando come esse si collochino lungo un continuum di cooperatività in senso griceano. Presenteremo poi le tre categorie operative delle nostre analisi: vaghezza lessicale, vaghezza sintattica e vaghezza da implicatura, quest’ultima suddivisa in vaghezza da implicatura particolarizzata, vaghezza da ironia, vaghezza da metafora e vaghezza da iperbole. Ciascuna categoria operativa viene presentata con numerosi esempi tratti dal discorso pubblico persuasivo contemporaneo in diverse lingue. Linguistic vagueness as an implicit persuasive strategy and a phenomenon at the interface between semantics, syntax and pragmatics. Examples from contemporary public discourse in different languages This work presents a pragmatic-cognitive model for analyzing the phenomenon of linguistic vagueness as an implicit persuasive and potentially manipulative strategy. In our study, we will delineate the difference between the concepts of systemic vagueness, soritical vagueness, and intentional vagueness. The latter will be the focus of the analyses presented here. The work introduces the notion of implicating vagueness and provides an overview of the main functions of intentional vagueness, showing how they fit along a continuum of Gricean cooperativeness. We will present the three operative categories of our analyses: lexical vagueness, syntactic vagueness, and implicature-based vagueness, the latter being divided into particularized implicature vagueness, irony vagueness, metaphorical vagueness, and hyperbolic vagueness. Each operative category is illustrated with numerous examples from contemporary persuasive public discourse in various languages.